Marine Bioactive Compounds Sources, Characterization and Applications - Hayes, Maria; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2012)
This book aims to bring together the areas of macroalgal taxonomy with strategies and methods used to characterise marine bioactive compounds. In addition, it looks at the importance of correct taxonomic characterization. It also describes applications of bioactive compounds from the marine environment and discusses how marine bioactive compounds represent a major market application in food and other industries.  It provides examples of bioactive compounds isolated from marine resources.   Examples are given as to how bioactive compounds have been used in functional food formulations and pharmaceutical applications, and how they alter biological activity to provide therapeutic benefits, nutritional values and health protection.   It looks at the screening process for identification of bioactive molecules including computing methods for efficient in silico analysis, and describes different production methods used for bioactive compound isolation and identification. Furthermore, this book provides an insight into the market opportunities that exist for the identification and commercialization of new marine bioactive compounds.  It also highlights regulations in the US, Europe, Japan and China regarding health or novel food claims for functional food products.   .
1. Taxonomy of Marine Macroalgae Used as Sources of Bioactive Compounds -- 2. Extraction and Characterization of Bioactive Compounds with Health Benefits from Marine Resources: Macro- and Microalgae Cyanobacteria and Invertebrates -- 3. Marine Bioactive Peptides and Protein Hydrolysates: Generation, Isolation Procedures and Biological and Chemical Characterizations -- 4. Chitin, Chitosan and Their Derivatives from Marine Rest-Raw Materials: Potential Food and Pharmaceutical Applications -- 5. Industry Potential of Marine Bioactive Components: Downstream Processing and Vehicles for Efficient Delivery in situ -- 6. Extraction and Characterization of Bioactive Carbohydrates with Health Benefits from Marine Resources: Macro- and Microalgae, Cyanobacteria and Invertebrates -- 7. Medicinal Chemistry and Ligand Profiling for Evaluation of Promising Marine Bioactive Molecules -- 8. Marine-Derived Functional Foods: Claims and Current Legislation.
Keywords: Pharmaceutical technology; Bioorganic chemistry; Pharmacy; Microbiology; Pharmaceutical Sciences/Technology.; Bioorganic Chemistry; Pharmacy; Microbiology